New Zero Power Memristor Emulator Model and Its Application in Memristive Neural Computation - Kumar, Prashant; Srivastava, Pushkar; Ranjan, Rajeev Kumar; Kumngern, Montree (My University, 2023)
We present here a simple three P-type MOSFET-based grounded memristor emulator model. The model is designed to achieve zero static power dissipation and is done so by eliminating the external DC supply i.e., no DC bias. The proposed memristor emulator model has extremely low dynamic power dissipation as well which comes to around 175 nW i.e., ∼ 67% improvement compared to recent work. A mathematical analysis is carried out to present the relevance of this design. Simulations were done on Cadence Virtuoso 90 nm technology node and fingerprints of the proposed memristor emulator were obtained. The layout area occupied by the model is approx 1154.69 μ m2 and an external capacitor is connected to add tunability to the circuit. Furthermore, Monte Carlo and corner analysis validate the robust nature of the design. Besides, simulations have been experimentally verified using CD-4007 CMOS integrated circuit (IC) to make the design practically feasible. Furthermore, the design offers advantages such as extremely less overall power consumption and smaller chip area that could possibly pave the path for fabrication using standard CMOS technologies. At last, an application of the proposed model depicting in-memory computation through a memristor emulator crossbar array is presented in brief.
Keywords: CMOS; in-memory computation; Memristor emulator; Monte Carlo; pinched hysteresis loop (PHL)